A metal–carbene template approach enables efficient synthesis of a functionalized cage-annulated crown ether. Issue 69 (6th August 2021) - Chang, Jin-Ping; Sun, Li-Ying; Zhang, Zi-En; An, Yuan-Yuan; Zhang, Le; Yu, Jian-Gang; Han, Ying-Feng
Abstract : A novel flexible intramolecular cage-annulated crown ether organic imidazolium cation with potentially large cavities was constructed through a kind of post-assembly modification strategy, photochemical [2+2] cycloaddition reaction. Abstract : A facile synthetic method to form cage-annulated crown ether with anchored imidazolium units was developed. The present work verified the potential application of the metal–carbene template approach (MCTA) in the preparation of novel flexible polyimidazolium cages by photochemical [2+2] cycloaddition reactions and may provide a new method for the preparation of flexible pure organic cages with incorporation of a variety of functional sites.